Effect of a combination of whole-body vibration and low resistance jump training on neural adaptation - Wang, H.-K.; Un, C.-P.; Lin, K.-H.; Chang, E.-C.; Shiang, T. Y.; Su, S.-C. (Research in Sports Medicine, 2014)
This study investigated and compared the effects of an eight-week program of whole body vibration combined with counter-movement jumping (WBV + CMJ) or counter-movement jumping (CMJ) alone on players. Twenty-four men`s volleyball players of league A or B were randomized to the WBV + CMJ or CMJ groups (n = 12 and 12; mean [SD] age of 21.4 [2.2] and 21.7 [2.2] y; height of 175.6 [4.6] and 177.6 [3.9] cm; and weight, 69.9 [12.8] and 70.5 [10.7] kg, respectively). The pre- and post-training values of the following measurements were compared: H-reflex, first volitional (V)-wave, rate of electromyography rise (RER) in the triceps surae and absolute rate of force development (RFD) in plantarflexion and vertical jump height. After training, the WBV + CMJ group exhibited increases in H reflexes (p = 0.029 and <0.001); V-wave (p < 0.001); RER (p = 0.003 and <0.001); jump height (p < 0.001); and RFD (p = 0.006 and <0.001). The post-training values of V wave (p = 0.006) and RFD at 0-50 (p = 0.009) and 0-200 ms (p = 0.008) in the WBV + CMJ group were greater than those in the CMJ group. This study shows that a combination of WBV and power exercise could impact neural adaptation and leads to greater fast force capacity than power exercise alone in male players